Relationship Between Serum Concentration of Adrenomedullin and Myocardial Ischemic T Wave Changes in Patients With Lung Cancer - Wu, Chen; Lin, Da-wei; Jiang, Yi-wen; Jiang, Feng; Wang, Zhao-xia; Wang, Yao-sheng (Frontiers in Cardiovascular Medicine, 2022)
Background Patients with lung cancer are at increased risk for the development of cardiovascular diseases. Molecular markers for early diagnosis of cardiac ischemia are of great significance for the early prevention of cardiovascular events in patients with lung cancer. By evaluating the relationship between adrenomedullin (ADM) and myocardial ischemic T wave changes, the clinical value of circulating ADM as a predictor of myocardial ischemia in patients with lung cancer is confirmed. Methods We enrolled patients with lung cancer and healthy people from 2019 to 2021 and extracted a detailed ECG parameter. After adjustment for potential confounders, logistic regression was used to assess the association of clinical data. We performed analyses on differences in T wave between patients with lung cancer and healthy people, and the relationship between T wave and ADM among patients with lung cancer. Receiver operator characteristic (ROC) curves were drawn to confirm the diagnostic value of biomarkers. Results After adjusting for potential confounders, the incidence of T wave inversion or flattening in patients with lung cancer was higher than in healthy people (OR: 3.3228, P = 0.02). Also, further analysis of the data of lung cancer patients revealed that the ADM in lung cancer patients with T wave inversion or flat was higher than those with normal T wave (189.8 ± 51.9 vs. 131.9 ± 38.4, p < 0.001). The area under the ROC curve was 0.8137. Conclusion Among the patients with lung cancer, serum ADM concentration is associated with the incidence of the abnormal T wave. ADM might be a potentially valuable predictor for heart ischemia in patients with lung cancer.